2020
DOI: 10.3727/105221620x15889714507961
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of p16 Decreases Biliary Damage and Liver Fibrosis in the Mdr2/ Mouse Model of Primary Sclerosing Cholangitis

Abstract: Biliary senescence and hepatic fibrosis are hallmarks of cholangiopathies including primary sclerosing cholangitis (PSC). Senescent cholangiocytes display senescence-associated secretory phenotypes (SASPs, e. g., TGF-β1) that further increase biliary senescence (by an autocrine loop) and trigger liver fibrosis by paracrine mechanisms. To determine the effect of p16 inhibition and role of the TGF-β1/miR-34a/SIRT1 axis in biliary damage and liver fibrosis in the Mdr2-/- mouse model of PSC. We treated (i) in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 44 publications
2
28
1
Order By: Relevance
“…As predicted, the absence of p16 INK4a in the liver decreased inflammation and fibrosis at two months. In accordance with our results, previous studies have demonstrated that removal of senescent cells reversed fibrosis and inflammation in atherosclerosis, pulmonary fibrosis, steatosis, and sclerosing cholangitis (17)(18)(19)31). Numerous studies have now discovered compounds that mimic the effects of these transgenic murine models.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As predicted, the absence of p16 INK4a in the liver decreased inflammation and fibrosis at two months. In accordance with our results, previous studies have demonstrated that removal of senescent cells reversed fibrosis and inflammation in atherosclerosis, pulmonary fibrosis, steatosis, and sclerosing cholangitis (17)(18)(19)31). Numerous studies have now discovered compounds that mimic the effects of these transgenic murine models.…”
Section: Discussionsupporting
confidence: 92%
“…In accordance with these results, previous studies demonstrated that removal of senescent cells reversed fibrosis and inflammation in atherosclerosis, pulmonary fibrosis, steatosis, and sclerosing cholangitis. [17] , [18] , [19] , 31 Numerous studies have now discovered compounds that mimic the effects of these transgenic murine models. The term ‘Senolytics’ has come to be used to refer to compounds that selectively kill senescent cells.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, we found that low CDKN2A expression in tumors of 6 different types, including melanoma and pancreatic adenocarcinoma, correlated with a decreased SASP signature [ 18 ], further demonstrating the role of p16 in regulation of the SASP. Consistent with our observation, other articles have found decreased expression of SASP factors upon suppression of p16 in a murine model of intervertebral disc regeneration [ 95 ] and liver fibrosis [ 96 ]. Interestingly, induction of senescence through p16 overexpression does not increase SASP gene expression [ 50 ], suggesting that p16 is necessary but not sufficient to induce the SASP.…”
Section: P16 Regulation Of Tumor Immunitysupporting
confidence: 93%
“…However, data regarding cellular senescence in PSC are scant, mainly from end stage disease, and nothing is known about its clinical meaning. Interestingly, recent data on mouse models of chronic cholestatic liver disease showed CS involvement in cholestatic damage and fibrosis, which can ameliorate after specific interventions targeting CS [14,15]. Therefore, the aim of our study was to evaluate the hepatic tissue expression of CS markers in liver samples from PSC patients in different histological stages, and analyze its correlation with clinical-pathological features and patients' prognosis.…”
Section: Highlightsmentioning
confidence: 98%
“…Interestingly, recent data on mouse models of chronic cholestatic liver disease showed CS involvement in cholestatic damage and fibrosis, which can ameliorate after specific interventions targeting CS. 14 , 15 …”
Section: Introductionmentioning
confidence: 99%